FileMaker 8 calculation functions - Love, Scott (Que, 2006)
The calculation dialog in FileMaker serves as a fundamental element in nearly all development activities. The calculation dialog allows developers easy access to the data fields in their solutions and to a complete function list. This Short Cut presents a complete description of each calculation function, lists examples, and in many cases offers additional comments on usage. This Short Cut is Chapter 6 from the book FileMaker 8 Functions and Scripts Desk Reference by Scott Love, Steve Lane, and Bob Bowers (0-7897-3511-3). As such, it contains references pointing you to additional information not found in this Short Cut, but in a companion book, Special Edition Using FileMaker 8 . Apart from this reference, the Short Cut is fully self-contained and is an excellent sampling of calculation functions.